Posouzení informačního systému firmy a návrh změn - Fremel, Karel (Vysoké učení technické v Brně. Fakulta podnikatelská, 2015)
Diplomová práce se zabývá analýzou informačního systému podniku a návrhem změn. V teoretické části diplomové práce je rozebrána problematika a pojmy z oblasti informačních systémů. Prostřednictvím vybraných metod analýz je posouzen současný stav informačního systému. Na základě výsledků těchto analýz je vypracován návrh změn.

The master‘s thesis foceses on the analysis of inforamtion system and makes proposal for ICT modification. The theoretical part of the thesis analyzes problems and terms concerning information systems. The thesis via selected analytical methods assesses the current state of the information system. Based on the outcome of the analytical methods, is made proposal for ICT modification.
Information System Efectiveness Assessment and Proposal for ICT Modification
Keywords: Informační systém; posouzení; návrh změn; Information system; assessment; proposal for modification